2001
DOI: 10.1038/sj.bmt.1703038
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of intravascular malignant lymphomatosis with high-dose chemotherapy and autologous peripheral blood stem cell transplantation

Abstract: Summary:Intravascular malignant lymphocytosis (IML) is a rare systemic disease characterized by proliferation of malignant B (rarely T) lymphoid cells within the lumina of small arteries, veins, and capillaries. Diagnosis requires skin, liver, renal, meningeal, or brain biopsy, but is rarely made ante mortem. In this report, we describe a patient who had an ante mortem diagnosis of IML as a result of a skin biopsy. Autologous peripheral blood stem cell transplantation (auto-PBSCT) was successfully performed af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(34 citation statements)
references
References 10 publications
1
33
0
Order By: Relevance
“…3 At the time of analysis, the combination of rituximab and chemotherapy has been reported to have been used in 15 patients (six in our series), resulting in complete remission in 11 of 12 evaluable patients, and no relapses at a median followup of 15 months; this combined strategy seems to be advisable in patients with CD20-positive IVL. Consolidation with high-dose chemotherapy supported by autologous stem cell transplantation may improve current outcomes, [21][22][23] even among J-HPC patients. 9 The application of such a strategy is, however, greatly limited by the high median age and poor PS of IVL patients.…”
Section: Discussionmentioning
confidence: 99%
“…3 At the time of analysis, the combination of rituximab and chemotherapy has been reported to have been used in 15 patients (six in our series), resulting in complete remission in 11 of 12 evaluable patients, and no relapses at a median followup of 15 months; this combined strategy seems to be advisable in patients with CD20-positive IVL. Consolidation with high-dose chemotherapy supported by autologous stem cell transplantation may improve current outcomes, [21][22][23] even among J-HPC patients. 9 The application of such a strategy is, however, greatly limited by the high median age and poor PS of IVL patients.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, two cases report sustained remissions after monotherapy with rituximab [43,44]. There are now seven case reports of long-term survival after autologous hematopoietic stem cell transplantation: three patients in first CR (one with CNS involvement) [40,45]; four in second CR [46][47][48][49]; and two patients in whom bone marrow transplant in second CR was unsuccessful [40].…”
Section: Therapymentioning
confidence: 99%
“…[2][3][4] High-dose chemotherapy (HDC) followed by autologous PBSC transplantation (auto-PBSCT) might be an efficient treatment; however, there are insufficient data to support the efficacy of HDC/auto-PBSCT against IVLBCL. 2,5,6 A recent report demonstrated that up-front HDC/ auto-PBSCT improved the 2-year PFS to 69% in patients with international prognostic index (IPI) high/intermediate or high-risk DLBCL and responses to induction therapy, in comparison to the 2-year PFS of 55% in patients with induction therapy alone. 7 As most patients with IVLBCL were classified into the IPI high-risk group, the up-front HDC/auto-PBSCT during the first CR may represent a useful treatment option for patients with IVLBCL.…”
mentioning
confidence: 99%